Horse flies (Diptera: Tabanidae) of three West African countries: A faunistic update, barcoding analysis and trypanosome occurrence - Votýpka, Jan; Brzoňová, Jana; Ježek, Jan; Modrý, David (Acta tropica, 2019)
Horse flies (Diptera: Tabanidae) are of medical and veterinary importance since they transmit a range of pathogens. The horse fly fauna of tropical Africa is still poorly known, and in some geographical areas has not been studied for decades. This study summarizes the results of tabanid collections performed in three West African countries where only sparse data were previously available, the Central African Republic (CAR), Gabon and Liberia. Of 1093 collected specimens, 28 morphospecies and 26 genospecies belonging to six genera were identified, including the first findings of eleven morphospecies in the countries where horse flies were collected: Philoliche (Subpangonia) gravoti Surcouf, 1908 and Tabanus ianthinus Surcouf, 1907 are new records for Liberia; Ancala fasciata f. mixta (Surcouf, 1914), Tabanus fraternus Macquart, 1846, and T. triquetrornatus Carter, 1915 for CAR; Chrysops longicornis Macquart, 1838, Haematopota albihirta Karsch, 1887, H. bowdeni Oldroyd, 1952, and H. brucei Austen, 1908 for Gabon; and Tabanus secedens f. regnaulti Surcouf, 1912 and T. thoracinus Palisot de Beauvois, 1807 for Gabon and Liberia. Species identification of all 28 morphospecies based on morphological features was further supplemented by barcoding of cytochrome oxidase I (COI). Based on the COI sequences of 115 specimens representing 74 haplotypes, a phylogenetic tree was constructed to illustrate the relationships among the tabanid species found and to demonstrate their intra- and interspecific divergences. Our study enriches the current number of barcoded tabanids with another 22 genospecies. Based on the analysis of molecular data we question the taxonomic relevance of the morphological forms Ancala fasciata f. mixta and Tabanus secedens f. regnaulti. A parasitological survey based on nested PCR of 18S rRNA revealed a high (˜25%) prevalence of Trypanosoma theileri in the studied horse flies, accompanied by two species of monoxenous trypanosomatids, Crithidia mellificae and Blastocrithidia sp.
Keywords: Trypanosoma; zvířata; Diptera; Africa, Western; DNA Barcoding, Taxonomic; taxonomické DNA čárové kódování; Animals; fylogeneze; Phylogeny; západní Afrika